INDIAN EMERGENCIES: BARANĪ'S FATĀWĀ-I JAHĀNDĀRĪ, THE DISEASES OF THE BODY POLITIC, AND MACHIAVELLI'S ACCIDENTI. - Syros, Vasileios (Philosophy East & West: A Quarterly of Comparative Philosophy, 2012)
This essay proposes a novel interpretation of the Fatāwā-i Jahāndārī (Precepts of world rulership), one of the major sources of Indo-Islamic political thought produced by Ziyāʾ al-Dīn Baranī, a seminal Indo-Islamic political theorist and historian (fourteenth century). It shows that one of the main thrusts of Baranī's theory is to offer a comprehensive account of the various kinds and manifestations of emergencies and modes of treating the diseases afflicting the body politic. It also investigates the ways in which Baranī's ideas on emergencies relate to the political circumstances that prevailed during the Delhi Sultanate period as well as to previous works of political and moral advice, particularly Nas īr al-Dīn Tūsī's Nasirean Ethics. In addition, this essay is the first systematic endeavor to place Baranī in conversation with Western political writers, especially Niccolò Machiavelli. It explores the affinities between these two authors' views on emergencies and, more broadly, on the challenges associated with rulership and the qualities requisite for an efficient ruler. My analysis of Baranī's ideas within the context of the Islamic tradition and the cross-cultural comparison with Machiavelli highlights the normative dimensions of his theory and its relevance to current debates on emergencies.